Modified selective way based trace cache - Jaison J.; Mukherjee P.K. (My University, 2025)
Performance efficient instruction fetch unit is a critical issue in superscalar processor design [1]. Trace cache which stores traces of the dynamic instruction stream is a major part of such fetch units. Conventional trace cache was implemented as a set associative structure where it is needed to probe all the ways in the particular set in order to look for the required entry [2]. Selective way based trace cache (SWTC) was a modified trace cache where only the selected way(s) are probed instead of probing all the ways [3]. Here, traces are divided into several types and stored into cache by type. In this paper, the mapping policy of the SWTC is used to propose a modified design. Simulation results show that the proposed design performs better than the earlier SWTC model. On comparing with the trace cache(TC), the proposed design shows a 4.68% improvement in performance in terms of instructions committed per cycle (IPC). © 2014 IEEE.